Iran’s Fight against International Terrorism - G. G. Machitidze (Vestnik MGIMO-Universiteta, 2020)
Abstract: The article analyzes the reasons that prompted the Arab states to consolidate their efforts and create the League of Arab States. Attention is focused on the deep differences that existed between the states that came forward with the idea of strengthening Arab unity and determined the nature of this regional organization and the features of its charter, which provided its members with the opportunity to preserve their political system, sovereignty and the specifics of foreign policy.The heterogeneous nature of LAS had an impact on its the goals and objectives. The focus of this organization was to protect pan-Arab interests and support all Arab states in achieving political independence.The aggravation of the situation in Palestine after the Second World War became a central item on the agenda of all the Arab League meetings. This organization indicated its position on the Palestinian issue in the preparatory period for its official proclamation. The article discusses the activities of the Arab League, aimed at introducing a complete boycott of Israel, which, amid expansion of the Arab League, other Arab states also joined. The Arab-Israeli conflict, due to the targeted efforts of the Arab League, consolidated the Arab geopolitical community and contributed to the formation of a national Arab identity. The LAS in its documents built a common Arab narrative, having two underpinnings: the recognition of the Palestinian Arab people as a victim of the Western powers and Zionists, as well as foreign policy of Israel.The article traces the relationship between the activities of the Arab League and the changes that have occurred in the regional and international environment. The gradual transition of the Arab League to the search for a political settleme maintain Arab unity by using the traditional tool – the unresolved Arab-Israeli conflict. The LAS member-states should have taken a pan-Arab stance on the settlement of the Arab-Israeli conflict in order to preserve national identity. The refusal of all Arab League members to accept the American settlement plan, proposed by D. Trump administration in early 2020, was a confirmation that this regional organization retains its position as a defender of Arab unity and pan-Arab interests.